(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Ankylosing spondylitis (AS) is a chronic rheumatic inflammatory disease that predominantly impacts the axial skeleton. Although it may also affect the peripheral joints, entheses, and extra-articular organs like the lungs, heart, and eyes, its incidence is comparatively lower. The impact of AS on an individual’s health-related quality of life is significant. Patients with AS who are unable to work have a substantially diminished quality of life.